Analysis of the role of mutations in the KMT2D histone lysine methyltransferase in bladder cancer. Issue 4 (21st February 2019) - Ding, Beichen; Yan, Libin; Zhang, Yucong; Wang, Zhize; Zhang, Yangjun; Xia, Ding; Ye, Zhangqun; Xu, Hua
Abstract : Histone lysine methyltransferases (HMT) comprise a subclass of epigenetic regulators; dysregulation of these enzymes affects gene expression, which may lead to tumorigenesis. Here, we performed an integrated analysis of 50 HMTs in bladder cancer and found intrinsic links between copy number alterations, mutations, gene expression levels, and clinical outcomes. Through integrative analysis, we identified six HMT genes ( PRDM9, ASH1L, SETD3, SETD5, WHSC1L1, and KMT2D ) that may play a key role in the development and progression of bladder cancer. Of these six HMTs, histone lysine N ‐methyltransferase 2D ( KMT2D ) exhibited the highest mutation rate in bladder cancer. Our comparison of the mRNA and miRNA expression profiles of mutated and wild‐type KMT2D suggested that two signaling pathways (FOX1–miR‐1224‐5p–DLK1 and HIF/GATA5–miR‐133a‐3p–DRD5) may mediate the tumor suppressive effect of the KMT2D mutation. In summary, our findings indicate that mutations in HMT genes, especially KMT2D mutation, may play a role in the development of bladder cancer. Abstract : KMT2D exhibits the highest mutation rate of examined histone methyltransferase (HMT) genes in bladder cancer (BCa). Comparison of mRNA and miRNA expression profiles of mutated and wild‐type KMT2D suggests two signaling pathways (FOX1–miR‐1224‐5p–DLK1 and HIF/GATA5–miR‐133a‐3p–DRD5) may mediate the tumor suppressive effect of the KMT2D mutation. Our findings indicate that mutations in HMT genes, especially the KMT2D mutation, may play a role in the development of BCa.